1991
DOI: 10.1055/s-2007-1003670
|View full text |Cite
|
Sign up to set email alerts
|

Diacylglycerols Modulate Insulin Action in Rat Adipocytes

Abstract: Effect of 1,2-diacylglycerols on the insulin receptor function and insulin action in rat adipocytes was studied. 1,2-dioctanoylglycerol (100 micrograms/ml) did not alter insulin binding but it did stimulate phosphorylation of the beta-subunit of the insulin receptor as well as its tyrosine kinase activity. However, dioctanoylglycerol inhibited insulin-stimulated receptor autophosphorylation. This concentration of dioctanoylglycerol inhibited insulin-stimulated CO2 metabolism, lipogenesis and 3-O-methyl-glucose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

1993
1993
1995
1995

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
0
1
Order By: Relevance
“…Therefore the only noncationic hexagonal phase promoter included in these studies was DiC8. Although we did not observe an effect of DiC8 on receptor phosphorylation in NIH 3T3 HIR 3.5 cells, studies in rat adipocytes showed a stimulation of insulin receptor tyrosine phosphorylation in response to this additive (Terry et al, 1991). Studies in cultured human monocytes and lymphoblastoid cells also showed increased tyrosine kinase activity both in intact cells and with the isolated insulin receptor (Grunberger & Levy, 1990).…”
Section: Discussioncontrasting
confidence: 84%
“…Therefore the only noncationic hexagonal phase promoter included in these studies was DiC8. Although we did not observe an effect of DiC8 on receptor phosphorylation in NIH 3T3 HIR 3.5 cells, studies in rat adipocytes showed a stimulation of insulin receptor tyrosine phosphorylation in response to this additive (Terry et al, 1991). Studies in cultured human monocytes and lymphoblastoid cells also showed increased tyrosine kinase activity both in intact cells and with the isolated insulin receptor (Grunberger & Levy, 1990).…”
Section: Discussioncontrasting
confidence: 84%